A Systematic Review of Empirical Research on Payment of Ecosystem Services and Farm Household Income in China - Bohao Jin; Heming Wang (SAGE Open)
The payment for ecosystem services (PES) scheme shows great poverty alleviation potential and recognizing this connection contributes to enhancing the development of residents in ecologically endowed areas. However, the literature has not clarified the extent of the promotion and moderating factors of PES on income yet. This study pursues the goal of identifying the effect of PES on household income in rural China from the income structure perspective. Methodologically, this research conducts a literature review of 28 papers to outline the effect of PES on agricultural production, off-farm, and total income, and it applies a meta-analysis and meta-regression analysis of 13 papers to identify the influencing degree and interference factors. The findings reveal four issues. Overall, the effect of PES on agricultural production income was negative, while the effect on off-farm and total income was positive. Second, the PES schemes boosted farm household income by 0.15 weighted average effect size. Third, farm household participation area, subsidized unit prices, and urbanization level played positive moderating effects, while farm household age was a negative moderating variable. Lastly, PES risk exacerbated income inequality among farm households. The study also integrates the PES and the SDGs, proposing that advancing climate action involves the assistance of sustainable communities, decent work, and protection from conflict with social equity. Finally, the paper provides recommendations in terms of government-led PES projects that should be inclusive of economic, social, and ecological objectives, provide job security for smallholders, and quality urbanization.